Isovalent vs. aliovalent transition metal doping of zinc oxide lithium-ion battery anodes — in-depth investigation by ex situ and operando X-ray absorption spectroscopy. (June 2021) - Trapananti, A.; Eisenmann, T.; Giuli, G.; Mueller, F.; Moretti, A.; Passerini, S.; Bresser, D.
Abstract: The precise determination of de-/lithiation mechanisms in alternative lithium-ion battery electrode materials is crucial for their potential future success, but quite challenging — e.g., due to the occurrence of multiple crystalline and (frequently) amorphous phases. Herein, we report an in-depth ex situ / operando characterization of (carbon-coated) Fe- and Co-doped zinc oxide anodes via X-ray absorption spectroscopy to probe the oxidation state and local structural environment of the different metals upon de-/lithiation. The results provide fundamental insights into the mechanism of the conversion and alloying reaction taking place for these two active materials. In addition, this comparative investigation allows for an evaluation of the impact of isovalent (Co 2+ ) and aliovalent (Fe 3+ ) doping on the lithiation mechanism, having an impact on the initial lithiation kinetics, while both dopants generally enable a greatly increased re-oxidation of zinc compared to pure zinc oxide and, thus, a more reversible conversion reaction. Graphical abstract: Image 1 Highlights: Atomic-scale and comparative understanding of the lithiation of Fe- and Co-doped ZnO by XAS. The reduction of iron occurs at significantly higher potentials than cobalt. The presence of metallic iron kinetically favors also the reduction of zinc. Very small and/or highly defective metallic iron/cobalt nanograins are formed at low potentials. Both dopants greatly enhance the reversibility of the conversion reaction.